Electrical properties of α-Ir2O3/α-Ga2O3 pn heterojunction diode and band alignment of the heterostructure - Kan, Shin-ichi; Takemoto, Shu; Kaneko, Kentaro; Takahashi, Isao; Sugimoto, Masahiro; Shinohe, Takashi; Fujita, Shizuo (Applied physics letters, 2018)
Corundum-structured iridium oxide (α-Ir2O3), showing p-type conductivity, is a strong candidate to form high-quality pn heterojunctions with α-Ga2O3. We fabricated α-Ir2O3/α-Ga2O3 pn heterojunction diodes and they showed well-defined rectifying current-voltage (I-V) characteristics with the turn-on voltage of about 2.0 V. The band alignment at the α-Ir2O3/α-Ga2O3 interface was investigated by X-ray photoemission spectroscopy, revealing a staggered-gap (type-II) with the valence- and conduction-band offsets of 3.34 eV and 1.04 eV, respectively. The total barrier height for electrons was about 2.4 eV, which reasonably agreed with the turn-on voltage in the I-V characteristics. This means that electrons are mainly attributed to electrical conduction around the turn-on voltage.